2023
DOI: 10.1186/s40478-023-01617-7
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis induces detrimental effects in chronic EAE and its implications for progressive MS

Abstract: Ferroptosis is a form of lipid peroxidation-mediated cell death and damage triggered by excess iron and insufficiency in the glutathione antioxidant pathway. Oxidative stress is thought to play a crucial role in progressive forms of multiple sclerosis (MS) in which iron deposition occurs. In this study we assessed if ferroptosis plays a role in a chronic form of experimental autoimmune encephalomyelitis (CH-EAE), a mouse model used to study MS. Changes were detected in the mRNA levels of several ferroptosis ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 81 publications
(133 reference statements)
0
13
0
Order By: Relevance
“… 6 The ferroptotic signalling pathway and its resulting phenotypes can be alleviated by anti‐ferroptotic compounds. 6 , 48 …”
Section: Discussionmentioning
confidence: 99%
“… 6 The ferroptotic signalling pathway and its resulting phenotypes can be alleviated by anti‐ferroptotic compounds. 6 , 48 …”
Section: Discussionmentioning
confidence: 99%
“…Besides its contribution to microglia-related EAE disease severity and neuronal damage [ 26 ], the sensitization to ferroptosis by activation of NOX2 was suggested in cancers [ 27 ]. With regard to iron regulation and utilization, a recent study has presented the dysregulated expression of genes involved in these processes, following increased lipid peroxidation in a chronic EAE, but not a relapsing–remitting EAE model [ 9 ]. The complexity of disease, including relapse, remission and progression phases, was reflected by gene expression changes through stages of EAE, showing the peak of SLC11A2/DMT1 expression at the peak of chronic EAE, decreasing to pre-onset levels in the progressive stage.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study has shown that transcriptional changes related to ferroptosis were more prominent during acute EAE and relapse, while demyelination progressively increased over time [ 11 ]. Expression of GPX4 , often assigned as the hallmark defense enzyme in ferroptosis that is required for glutathione-mediated antioxidant defense, remained unchanged between RR and chronic EAE [ 9 ]. The GPX4 gene expression and plasma protein levels were not different between MS phenotypes in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jhelum et al [ 184 ] reported increased peroxidation, increased mRNA levels of several ferroptosis genes, increased nuclear receptor coactivator 4 (NCOA4) expression (assessed using qRT-PCR), decreased GPx4 activity (assessed using Western blot analysis), and decreased total glutathione (assessed using spectrophotometry) in the brain of female mice with EAE of C57BL/6. C57BL/6 OlaHSD [ 15 ] and C57BL/6 female mice with EAE [ 185 ] showed increased levels of acrolein or their metabolites (assessed using Western blot [ 15 ] or liquid chromatography/tandem mass spectrometry [ 185 ]) in the spinal cord and urine.…”
Section: Data From Experimental Models Of Multiple Sclerosismentioning
confidence: 99%

Oxidative Stress Markers in Multiple Sclerosis

Jiménez-Jiménez,
Alonso-Navarro,
Salgado-Cámara
et al. 2024
IJMS